0027 Learning To Interact With The Legal System Using Simulation In Psychiatry. (1st November 2014) - Wilson, Catherine; Reedy, Gabriel; Jabur, Zainab; Pathan, James; Campbell, Lloyd; Tritschler, Christina; Luff, Adrian; Cross, Sean
Abstract : Background/content: Simulation has been relatively under-used in psychiatric training 1 and has focused on psychiatric and medical emergencies. 2 However, other events, such as interaction with the legal system, have serious implications for mental health professionals' clinical practice but often little practical training is provided. In order to meet this need pilot courses were designed, developed and piloted to simulate legal aspects of psychiatric practice, in particular the coroner's inquest court and mental health tribunals, both situations which clinicians find anxiety provoking. 3 Methodology: Participants (n = 24) were asked to prepare reports prior to the course day based upon simulated casenotes. Participants presented their evidence in a simulated court or tribunal, consisting of a panel of judges and other relevant professionals, followed by a structured debrief. To balance fidelity with maximising learning, different models of organising the presentation of evidence and the debrief were piloted. Results/outcomes: Candidates filled out pre- and post-course questionnaires relating to knowledge, attitudes and confidence in these situations. Pre-course data for tribunals showed that participants felt that their "professional identity is threatened" by these situations or for the inquests that "relatives would blame me for the death". Participants lacked confidence in many aspects of both of these environments, for example around preparing reports or answering questions in court. Attitudes and confidence were positively affected by both courses and, although a significance analysis has not been conducted for the tribunal course, the results were statistically significant for the coroner's course. There was no change in levels of knowledge. All participants said they would recommend the course to their colleagues. Conclusions and recommendations: These pilots suggest that simulating legal aspects of mental health can improve confidence and change attitudes of healthcare professionals and appears to be a useful adjunct to the training of mental health professionals. Further research is ongoing. References: Dave S. Simulation in psychiatric teaching. Advances in Psychiatric Treatment 2012;18(4):292–298 Thomson AB, Cross S, Key S, et al . How we developed an emergency psychiatry training course for new residents using principles of high-fidelity simulation. Medical Teacher 2013;35(10):797–800 Calthorpe B, Choong S. The coroner's court and the psychiatrist. Advances in Psychiatric Treatment 2004;10(2):146–152